Reactive oxygen species‐mediated endoplasmic reticulum stress response induces apoptosis of Mycobacterium avium‐infected macrophages by activating regulated IRE1‐dependent decay pathway. (16th August 2019) - Go, Dam; Lee, Junghwan; Choi, Ji‐Ae; Cho, Soo‐Na; Kim, Seon‐Hwa; Son, Sang‐Hun; Song, Chang‐Hwa
Abstract: Mycobacterium avium, a slow‐growing nontuberculous mycobacterium, causes fever, diarrhoea, loss of appetite, and weight loss in immunocompromised people. We have proposed that endoplasmic reticulum (ER) stress‐mediated apoptosis plays a critical role in removing intracellular mycobacteria. In the present study, we investigated the role of the regulated IRE1‐dependent decay (RIDD) pathway in macrophages during M. avium infection based on its role in the regulation of gene expression. The inositol‐requiring enzyme 1 (IRE1)/apoptosis signal‐regulating kinase 1 (ASK1)/c‐Jun N‐terminal kinase (JNK) signalling pathway was activated in macrophages after infection with M. avium . The expression of RIDD‐associated genes, such as Bloc1s1 and St3gal5, was decreased in M. avium‐ infected macrophages. Interestingly, M. avium ‐induced apoptosis was significantly suppressed by pretreatment with irestatin (inhibitor of IRE1α) and 4μ8c (RIDD blocker). Macrophages pretreated with N ‐acetyl cysteine (NAC) showed decreased levels of reactive oxygen species (ROS), IRE1α, and apoptosis after M. avium infection. The expression of Bloc1s1 and St3gal5 was increased in NAC‐pretreated macrophages following infection with M. avium . Growth of M. avium was significantly increased in irestatin‐, 4μ8c‐, and NAC‐treated macrophages compared with the control. The data indicate that the ROS‐mediated ER stress response induces apoptosis of M. avium ‐infected macrophages by activating IRE1α‐RIDD. Thus, activation of IRE1α suppresses the intracellular survival of M. avium in macrophages.